SARS-CoV-2 and other emerging viruses and their relationship to safety in the food chain - Silva-Jaimes, Marcial (2020)
Influenza pandemics are related to the viral flow of wild and migratory birds, passing to pigs and poultry (intermediate hosts), which would end up infecting humans. Process management through Good Farming Practices for animal production and Animal Welfare should be important preventive measures to avoid this contagion. In coronaviruses and Ebola there are ancestral hosts (such as bats) and intermediate hosts (such as Civettictis civetta or Paradoxurus hermaphroditus for SARS-CoV-1, dromedaries for MERS-CoV, and snakes and Manis javanica for SARS-CoV-2). In its natural state the inter-specie jump would take much longer to occur; however, the existence of wet markets, where animals are traded, would have allowed viruses to find a new host in humans. In addition to pneumonia, the invasion of SARS-CoV-2 produces temporary discomfort, such as diarrhea, due to the abundance of the ACE-2 receptor in both lung cells and enterocytes, where its replication would increase the probability of transmission by the fecal-oral route. This risk could be minimized by improving Good Manufacturing Practice (GMP) procedures in the food industry. Future research should clarify the relationship between viruses and their hosts, as well as the effect of climate change and proteins availability for human consumption, on these pandemics.